Simple and clear differentiation of spinocerebellar degenerations: Overview of macroscopic and low‐power view findings. Issue 5 (20th July 2022) - Iwabuchi, Kiyoshi; Koyano, Shigeru; Yagishita, Saburo
Abstract : Spinocerebellar degenerations (SCDs) are a diverse group of rare and slowly progressive neurological diseases that include spinocerebellar ataxia type 1 (SCA1), SCA2, SCA3, SCA6, SCA7, dentatorubral‐pallidoluysian atrophy (DRPLA) and multiple system atrophy (MSA). They are often inherited, and affect the cerebellum and related pathways. The combination of clinical findings and lesion distribution has been the gold‐standard for classifying SCDs. This conventional approach has not been very successful in providing a solid framework shared among researchers because their points of views have been quite variable. After identification of genetic abnormalities, classification was overwhelmed by genotyping, replacing the conventional approach far behind. In this review, we describe a stepwise operational approach that we constructed based only on macroscopic findings without microscopy to classify SCDs into three major groups: pure cerebellar type for SCA6 and SCA31; olivopontocerebellar (OPC) type for SCA1, SCA2, SCA7 and MSA; and dentatorubral‐pallidoluysian (DRPL) type for SCA1, SCA3, DRPLA and progressive supranuclear palsy (PSP). Spinocerebellar tract involvement distinguishes SCA1 and SCA3 from DRPLA. Degeneration of the internal segment of the pallidum is accentuated in SCA3 and PSP, while degeneration of the external segment is accentuated in SCA1 and DRPLA. These contrasts are helpful in subdividing OPC and DRPL types to predict their genotypes. Lesion distribution represents disease‐specific selective vulnerability, which is readily differentiated macroscopically using our stepwise operational approach. Precise prediction of the major genotypes will provide a basis to understand how genetic abnormalities lead to corresponding phenotypes through disease‐specific selective vulnerabilities.